Respon Kombinasi Media Tanam dan Dosis Pupuk NPK Mutiara Terhadap Pertumbuhan dan Hasil Tanaman Terung (Solanum melongena L.) - Riskiyanti, Wahyuni; Silvia Fitri Mei Arini, Silvia (Program Studi Agroteknologi, 2025)
This research aims to determine the response of the combination of planting media and Npk Mutiara fertilizer to the growth and yield of eggplant plants (Solanum Melongena L.). This research was carried out in Kesilir Village, Wuluhan District, Jember Regency, East Java. Starting from April 2024 to June 2024. The research used a 3 x 5 Factorial Randomized Block Design with 3 replications. The first factor is the combination of different planting media with levels M1= Soil + manure + cocopeat, M2= Soil + manure + husk charcoal, M3= Soil + manure + sawdust. The second factor is the dose of pearl NPK fertilizer with 5 levels, namely: (control) P0 = 0 g/plant, P1 = 10 g/plant, P2 = 20 g/plant, P3 = 30 g/plant, P4= 40 g/plant. The data obtained were then analyzed using variance (ANOVA), if they were significantly different then continued with the Duncan test with a 5% level using Microsoft Excel. The results of the research showed that NPK fertilizer treatment had a good effect on plant height parameters. Dosing Mutiara NPK fertilizer had a very significant effect on the growth and production of eggplant plants, which gave the best response to the number of leaves. The use of different planting media had a significant effect on the number of leaves and fruit diameter. And the interaction between NPK Mutiara fertilizer and the planting medium provides a response to plant height.